Literacy in Digital Intimacy - A Key Competence for Youth Development - Vandenbosch , Laura (2025)
This trailer introduces digital intimacy literacy as a missing concept in debates on how to empower young people’s sexualities in today’s digital society. It suggests that while extensive literature exists on different subareas of digital intimacy and the development of users’ sexuality, they can be combined to yield a more comprehensive understanding of digital intimacy in youth. Such integration can be further enriched by taking into account insights from communication literature, including the need for age-appropriate media interactions and the hidden costs of technological efficiency. Advancing our knowledge of digital intimacy is key for conceptualizing digital intimacy literacy, which is considered an important tool to empower contemporary young media users’ sexuality. Digital intimacy literacy is framed as a unique construct which goes beyond traditional media literacy, encompassing interactive experiences, emotional responses, and sexuality at its core. Further research on digital intimacy literacy is essential to deepen our understanding of digital intimacy among youth—insights that can ultimately support their sexual flourishing.